Africa’s displaced people: Out of the shadows - André-Michel Essoungou (Africa Renewal, 2010)
It was a departure they never had time to prepare for. Seeking to escape death – sometimes amidst fighting between the Senegalese army and rebels in the southern region of Casamance – thousands fled their homes and abandoned livestock and property. Over the past two decades many have resettled in successive waves in Ziguinchor, a major city in Casamance.